Apple Pomace as Valuable Food Ingredient for Enhancing Nutritional and Antioxidant Properties of Italian Salami - Luca Grispoldi; Federica Ianni; Francesca Blasi; Luna Pollini; Silvia Crotti; Deborah Cruciani; Beniamino Terzo Cenci-Goga; Lina Cossignani (MDPI AG, 2022)
Nowadays, food fortification with bioactive compounds deriving from agri-food waste is of great interest all over the world. In this work, apple pomace (AP), the most abundant by-product of apple juice manufacturing, was characterised by chemical, chromatographic and spectrophotometric analyses. AP showed valuable antioxidant activity, due to the presence of phenolic compounds (8.56 mg gallic acid equivalents/g), including quercetin-3-O-galactoside, quercetin-3-O-arabinofuranoside, and phloridzin. Dried AP, at 7% and 14%, was added to pork meat to produce Italian salami, then subjected to 25 days of ripening. Physicochemical, colorimetric and microbiological analyses were carried out at days 0, 5, 11, 19 and 25, while nutritional and sensory evaluations were performed at the end of the ripening. The overall acceptability was slightly higher for 7% AP compared to 14% AP sample, and generally the replacement of a percentage of meat with apple pomace allowed the production of salami with sensory properties comparable to those obtained with classic recipes. The improved fibre and phenol content, together with the lower fat and calories, represent the most interesting characteristics of fortified salami. The results confirm that the addition of AP represents a valid approach to adding healthy compounds to salami.